The influence of hair lipids in ethnic hair properties. (7th September 2015) - Martí, M.; Barba, C.; Manich, A. M.; Rubio, L.; Alonso, C.; Coderch, L.
Abstract: Objective: Biochemical studies have mainly focused on the composition of hair. African hair exhibited lower moisturization and less radial swelling when flushing with water compared with Asian or Caucasian hair, and they assumed a possible lipid differentiation among human populations. This study consists in the lipid characterization of different ethnic hairs (Caucasian, Asian and African hairs) and the influence of these lipids in different hair properties such as humidity and mechanical properties. Evaluation of water sorption and desorption of the different ethnic hairs and with and without lipids is also studied mainly to determine permeation changes of the keratin fibres. Methods: Extractions of exogenous and endogenous lipids with different organic solvents were performed; lipid analysis and its quantification using thin‐layer chromatography coupled to an automated flame ionization detector (TLC/FID) were performed. Absorption and desorption curves were obtained in a thermogravimetric balance equipped with a controlled humidity chamber, the Q5000SA Sorption Analyzer (TA Instruments, New Castle, IL, U.S.A.). Also, mechanical properties (breaking stress and breaking elongation) were analysed using a computer programmable dynamometer (Instron 5500R). Results: Lipid extraction showed the highest amount of total lipids for the African hair which may come from external sebaceous lipids compared with Asian or Caucasian hair. Caucasian fibres were found to be the most hydrated fibre, and a decrease in moisture was found in the extracted fibres, again, which is more important for the Caucasian hair. A superior lineal mass was found for the Asian fibres which supported their higher strength. The results obtained from the analysis of the mechanical properties of delipidized fibres indicate a surprising increase in the strength of African and Caucasian fibres. Perhaps this increase in strength could be related to the humidity decrease in lipid‐extracted hair fibres. Results of water uptake and desorption indicate that Asian and Caucasian hairs present the lower diffusion coefficients compared with the African ones. At least for the African fibre, an extraction of its lipids that mainly account for apolar lipids ameliorates the fibre structure, decreasing its permeability to water and increasing its tensile strength. Conclusion: The ethnic hairs were assessed related to their lipid composition, and some differences between them were found in terms of water uptake and mechanical properties.